2003
DOI: 10.4141/a02-026
|View full text |Cite
|
Sign up to set email alerts
|

Cattle herbage utilization patterns under high-density rotational grazing in the Aspen Parkland

Abstract: . 2003. Cattle herbage utilization patterns under highdensity rotational grazing in the Aspen Parkland. Can. J. Anim. Sci. 83: 541-550. Native Aspen Parkland landscapes consist of a complex mosaic of plant communities, including riparian meadows, upland grasslands, and forests. Sustainable livestock production in this environment depends on an understanding of livestock grazing behavior among communities, particularly under contemporary, intensive management rotational grazing systems. This study examined seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Here we observed that Carex nigra, C. rostrata, C. lasiocarpa, C. vaginata and C. canescens were heavily grazed. These species are known to be valuable and nutrient-rich, especially with regard to protein concentration, and preferred by cattle in these types of pasture (Garmo 1986;Rekdal 2001;Asamoah et al 2003;Saether, Sickel, et al 2006;Jørgensen et al 2012).…”
Section: Parametermentioning
confidence: 96%
“…Here we observed that Carex nigra, C. rostrata, C. lasiocarpa, C. vaginata and C. canescens were heavily grazed. These species are known to be valuable and nutrient-rich, especially with regard to protein concentration, and preferred by cattle in these types of pasture (Garmo 1986;Rekdal 2001;Asamoah et al 2003;Saether, Sickel, et al 2006;Jørgensen et al 2012).…”
Section: Parametermentioning
confidence: 96%
“…North-facing slopes support vegetation with greater moisture requirements such as shrublands and deciduous forest, while south-facing slopes support plant communities tolerant of drier conditions such as grasslands (Coupland 1961;Wheeler 1976). Late summer dry matter herbage production from upland grassland, riparian meadow and forest vegetation averages 2062, 4862 and 1743 kg.ha -1 , respectively (Asamoah et al 2003). The major vegetation types found across the study area and of interest in this investigation are as follows:…”
Section: Study Areamentioning
confidence: 97%